2014
DOI: 10.1017/s104795111400136x
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol-induced ductal closure in a 5-month-old infant

Abstract: To the Editor, Recently, we cared for a 5-month-old baby boy born at 28 weeks gestation with a 1.9-mm patent ductus arteriosus (Fig 1). The parents were counselled regarding the plan for percutaneous device closure and asked to return 2 weeks later. Surprisingly, on repeat echocardiogram, the ductus arteriosus had closed. As spontaneous ductal closure is unusual past the newborn period, we questioned the parents about the events in the preceding 2 weeks. The parents reported administering paracetamol 12 mg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Is the next coming question. None of the reviewed papers showed that paracetamol therapy has been initiated before the age of 48 hours, this is going with the idea of high percentage of spontaneous closure of PDA in premature neonates by 48 hours of life as stated by Koch J et al (38), but it seems that there is no clear cut-off about the maximal postnatal age suitable for this therapy because a wide range of postnatal ages up to 47 days by Ozmert M. et al (27) have been included in the reviewed articles, however restricting this therapy to the neonatal period appears more logical although success outside this period has been reported by Cynthia H et al (18). Gestational age appears to be important among the treated patients because in 3 series with patients GA 23-27.9 weeks the success rates were the lowest ranging between 18.18-27.77% compared to the general success rate of 70-100 % for other more mature groups (24, 25, and 26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Is the next coming question. None of the reviewed papers showed that paracetamol therapy has been initiated before the age of 48 hours, this is going with the idea of high percentage of spontaneous closure of PDA in premature neonates by 48 hours of life as stated by Koch J et al (38), but it seems that there is no clear cut-off about the maximal postnatal age suitable for this therapy because a wide range of postnatal ages up to 47 days by Ozmert M. et al (27) have been included in the reviewed articles, however restricting this therapy to the neonatal period appears more logical although success outside this period has been reported by Cynthia H et al (18). Gestational age appears to be important among the treated patients because in 3 series with patients GA 23-27.9 weeks the success rates were the lowest ranging between 18.18-27.77% compared to the general success rate of 70-100 % for other more mature groups (24, 25, and 26).…”
Section: Discussionmentioning
confidence: 99%
“…Patients underwent daily evaluation using the same pretreatment parameters with daily echocardiographic evaluation. If the patient didn't show complete closure or significant ductal constriction a second course were given with the same evaluation method for the next 4-5 days regardless weather the patient already received one of the NSAIDs or not.The intended primary outcome of all reviewed papers were complete ductal closure or the development of significant ductal constriction (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) which is defined by the absence of shunt or diameter < 0.5 mm without any other hemodynamic implications at echocardiographic examination performed daily during the study period as described by Terrin G et al (22) .Secondary outcome of treated patients can be summarized as the need for surgical ligation of the PDA , mode and duration of ventilation; increase in blood urea nitrogen, serum creatinine, bilirubin, AST, or ALT levels after treatment, rates of ductal reopening, surfactant treatment, pneumothorax, pulmonary hemorrhage, Chronic lung disease, IVH, necrotizing enterocollitis (NEC), gastrointestinal bleeding, retinopathy of prematurity, definite sepsis, and death. It seems that the drug is a safe and none of the papers showed increase in the incidence of the complications when compared to the other NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N (number), GA (gestational age), PDA (patent ductus arteriosus), LA (left atrium), Ao (aortic), h (hour), NSAID (non-steroidal anti-inflammatory drugs), d (days), I.V (intravenous). Four case report articles were evaluated (15)(16)(17)(18), with the first one has been published in 2011 as shown in table (1).Only Hammerman c et al (15) gave clear definition of hds PDA which was a ductus with internal diameter more than 2 mm, left atrium to aortic ratio more than 1.48 and ductal internal diameter to aortic ratio more than 0.5 (15), while Alan S et al (16) considered left atrium to aortic ratio (LA/AO) of >1,57 as hds PDA and Cynthia H et al considered a PDA with an internal diameter of 1,9 mm as hds PDA. In all cases paracetamol was given in a dose of 15mg/kg/dose /6 hours for 48 hours regardless to the rout of administration except for Pérez Dominguez ME et al (17) who gave IV paracetamol in a dose of 7.5 mg/kg/6 hours to a premature neonate when it was necessary to give a second course of paracetamol and 12mg/kg/12 hours for 4 days given for a different purpose to the child as reported by Cynthia H et al (18) and all patients followed by echocardiographic evaluation for up to 1 week to give the final decision about ductal closure.…”
Section: Methods Of Searchmentioning
confidence: 99%